2018
DOI: 10.1002/pbc.27385
|View full text |Cite
|
Sign up to set email alerts
|

Combined high‐dose intra‐arterial and intrathecal chemotherapy for the treatment of a case of extraocular retinoblastoma

Abstract: Patients with retinoblastoma and central nervous system (CNS) involvement are rarely curable with available treatments. We designed a high-dose intra-arterial regimen targeting the ophthalmic artery and chiasm combined with intrathecal chemotherapy to treat a 4-year-old patient with retinoblastoma metastasized to the CNS. After three cycles of this regimen, including carboplatin, melphalan, and intrathecal topotecan, a partial response of the orbital tumor mass and chiasmatic lesion, and complete response in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Thereafter, the child was lost to follow-up and further status was not known on stability or recurrence or metastasis or death. [76]…”
Section: Treatment Outcomesmentioning
confidence: 99%
“…Thereafter, the child was lost to follow-up and further status was not known on stability or recurrence or metastasis or death. [76]…”
Section: Treatment Outcomesmentioning
confidence: 99%
“…However, the only survivor in the initial diagnosis group had positive MDD in the CSF at diagnosis, suggesting that intensive treatments may rescue these patients, as we reported in cases with high‐risk pathology features . Intra‐arterial chemotherapy may be considered as a way to achieve higher chemotherapy exposure to the optic nerve compared to systemic chemotherapy . Since a high proportion of our patients have MDD, in case intra‐arterial is used to treat orbital retinoblastoma, it should be combined with other systemic and CNS‐directed therapies.…”
Section: Discussionmentioning
confidence: 72%
“…11 Intra-arterial chemotherapy may be considered as a way to achieve higher chemotherapy exposure to the optic nerve compared to systemic chemotherapy. 15,16 Since a high proportion of our patients have MDD, in case intra-arterial is used to treat orbital retinoblastoma, it should be combined with other systemic and CNS-directed therapies.…”
Section: Discussionmentioning
confidence: 99%
“…While neural invasion predominantly lead to CNS metastases; non-neural invasion have higher propensity to metastasize to other systemic sites 21 . It has been reported that CNS metastases have worse prognosis compared to other systemic metastases due to the blood-brain barrier which does not permeate the systemic chemotherapy 19 and may warrant adjuvant intrathecal or intraventricular chemotherapy 22,23 . B7H3 expression showed a significant increase in the RB tumor invading non-neural tissues compared to neural tissues.…”
Section: Discussionmentioning
confidence: 99%